Cobalt-Catalyzed Oxidative C−H/C−H Cross-Coupling between Two Heteroarenes - Tan, Guangying; He, Shuang; Huang, Xiaolei; Liao, Xingrong; Cheng, Yangyang; You, Jingsong (Angewandte Chemie International Edition, 2016)
The first example of cobalt‐catalyzed oxidative C−H/C−H cross‐coupling between two heteroarenes is reported, which exhibits a broad substrate scope and a high tolerance level for sensitive functional groups. When the amount of Co(OAc)2⋅4 H2O is reduced from 6.0 to 0.5 mol %, an excellent yield is still obtained at an elevated temperature with a prolonged reaction time. The method can be extended to the reaction between an arene and a heteroarene. It is worth noting that the Ag2CO3 oxidant is renewable. Preliminary mechanistic studies by radical trapping experiments, hydrogen/deuterium exchange experiments, kinetic isotope effect, electron paramagnetic resonance (EPR), and high resolution mass spectrometry (HRMS) suggest that a single electron transfer (SET) pathway is operative, which is distinctly different from the dual C−H bond activation pathway that the well‐described oxidative C−H/C−H cross‐coupling reactions between two heteroarenes typically undergo. A bidentate 8‐quinolinyl ligand assists the cobalt‐catalyzed title reaction between two (hetero)arenes exhibiting a broad substrate scope and a high tolerance level for sensitive functional groups. The preliminary mechanistic study suggests that a single electron transfer pathway is operative.